A comparative study of the subjects on ecosystem, biological diversity and environmental problems in Turkish science curriculum with the ınternational curricula - Özata Yücel, Elif; Özkan, Muhlis (Journal of Turkish Science Education, 2014)
In this study, Turkey’s Science Curriculum 2013 was compared with that of the other countries (England, Ireland, Finland, Canada, New Zealand, and USA (New Jersey and Massachusetts)) that produced above the average results in TIMSS (1995, 1997, 2003 and 2007) exams in subjects on Ecosystem, Biological Diversity, and Environmental Problems. In terms of vision, the curricula of Finland and England lay greater emphasis on the ‘environment’. “Technology-society-environment” relations are emphasized in only Turkey’s Curriculum. Understanding and discovery of the natural world, gaining environmental knowledge, and man-environmental relations are included in Turkey’s curriculum in terms of aims. Besides, there has been an emphasis on the development of sustainable natural resources in Turkey’s curriculum; whereas biological diversity is excluded just as in the curricula of Finland, England, New Zealand, Ireland, and New Jersey. The goals related to the man-environment interaction are included in the curricula of Turkey; whereas, those related to the mutual relationship between otherliving things are not considered. This indicates that Turkey’s curriculum is anthropocentric. There have been variations in the composition of curricula of different countries compared with Turkey’s curriculum, in terms of organization of the subjects such as ecosystem, biological diversity, and environmental problems. There is no separate course in Turkish curriculum as in Finland, and no different learning strand as in the science curriculum of Ireland and New Jersey province of the USA. In the curricula under study, while there is one subject in a country’s curriculum, others may not have the same. Some of the countries determined the topics by giving importance to their local needs or adopted approaches that prevent learning environment as an integrated and universal subject. In order to overcome these deficiencies, it is imperative to design a universal environmental education.